In vitro activities of six antifungal agents and their combinations against Chaetomium spp. Issue 7 (29th May 2019) - Sun, Lingyue; Wan, Zhe; Li, Ruoyu; Yu, Jin
Abstract : Purpose. To assess in vitro activities of six antifungal agents (amphotericin B, itraconazole, voriconazole, posaconazole, caspofungin and terbinafine) and the combined effects of eight pairs of them (caspofungin or terbinafine with amphotericin B, itraconazole, voriconazole or posaconazole) against 22 isolates of Chaetomium spp. Methodology. The broth microdilution method drafted by the Clinical and Laboratory Standards Institute and the checkerboard method were used in this study to evaluate in vitro activities of antifungal drugs both alone and in combination against Chaetomium spp. Results. Amphotericin B and triazoles exhibited lower geometric mean, MIC50 and MIC90 than caspofungin and terbinafine. Besides, all the paired drugs displayed varying degrees of synergism, with the interactions between caspofungin and itraconazole ranking first (86.36 %). Conclusion. Our study illustrated varying degrees of synergism between caspofungin or terbinafine and itraconazole, voriconazole, posaconazole or amphotericin B towards Chaetomium spp., which could be a reference for the clinical treatment of Chaetomium spp. infections.